Gold vs rhodium catalysis: tuning reactivity through catalyst control in the C-H alkynylation of isoquinolones - Shaikh, Aslam C.; Shinde, Dinesh R.; Patil, Nitin T. (Organic Letters, 2016)
A site-selective C-4/C-8 alkynylation of isoquinolones catalyzed by gold and rhodium complexes is reported. A broad range of synthetically useful functional groups (-F, -Cl, -Br, -CF3, -OMe, alkyl, etc.) were tolerated, providing an efficient and robust protocol for the synthesis either C-4- or C-8-alkynylated isoquinolones.